2020
DOI: 10.3390/molecules25204646
|View full text |Cite
|
Sign up to set email alerts
|

Cornus mas L. Stones: A Valuable by-Product as an Ellagitannin Source with High Antioxidant Potential

Abstract: The stone of Cornus mas L. remains the least known morphological part of this plant, whereas the fruit is appreciated for both consumption purposes and biological activity. The stone is considered to be a byproduct of fruit processing and very little is known about its phytochemical composition and biological properties. In this study, the complete qualitative determination of hydrolyzable tannins, their quantitative analysis, total polyphenolic content, and antioxidant properties of the stone of C. mas are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…The use in folk medicine of these parts of the C. mas plant has been known and appreciated for many years, especially in Asia [4,8,[21][22][23][24][25][26][27][28][29]. Recent studies have proven that C. mas stones are a good source of various bioactive hydrolyzable tannins and show high antioxidant activity [30], while C. mas leaf extract contains a hydroxycinnamic acid derivatives, flavonols, ellagitannins, as well as iridoids, and shows high antibacterial activity against Gram-negative bacteria [31]. Moreover, latest research embraced evaluation of the unripe fruits towards the detection and isolation of biosynthetic precursors of compounds found in mature fruits [32].…”
Section: Introductionmentioning
confidence: 99%
“…The use in folk medicine of these parts of the C. mas plant has been known and appreciated for many years, especially in Asia [4,8,[21][22][23][24][25][26][27][28][29]. Recent studies have proven that C. mas stones are a good source of various bioactive hydrolyzable tannins and show high antioxidant activity [30], while C. mas leaf extract contains a hydroxycinnamic acid derivatives, flavonols, ellagitannins, as well as iridoids, and shows high antibacterial activity against Gram-negative bacteria [31]. Moreover, latest research embraced evaluation of the unripe fruits towards the detection and isolation of biosynthetic precursors of compounds found in mature fruits [32].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research showed that, regardless of the juice from the selected cultivar of Cornelian cherry fruit, after the fermentation stage, the content of gallic acid in the meads increased from 93% in the PF sample to 120% in the JF and KF samples. The content of gallic acid increased, probably as a result of hydrolysis of the high-molecular tannins contained in the Cornelian cherry [25]. An upward trend in the content of gallic acid by 8% was observed during the aging process of the JA mead.…”
Section: Phenolic Acidsmentioning
confidence: 93%
“…In other samples, the content of this compound during the aging process increased from 6.5% in the PA mead to 17% in the JA mead. Perhaps because during aging, cornuside is released from high-molecular tannins like other iridoids in Cornelian cherry [25], or the released gallic acid and loganine from high-molecular tannins connect to form cornuside, however this has not been confirmed in the scientific literature yet. Despite the fact that in some of the tested samples, the content of cornuside increased during aging, the entire technological process resulted in the reduction of the content of this compound in the final products from 32% in JA and PA to 41% in KA.…”
Section: Iridoidsmentioning
confidence: 98%
See 1 more Smart Citation
“…The total polyphenol content was determined by the spectrophotometric method with the Folin–Ciocalteu reagent. All determinations were performed in triplicates using Shimadzu UV–Vis 2401 PC spectrophotometer (Tokyo, Japan) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%